ANALYSIS OF POTENTIAL USE OF E-COMMERCE DURING THE COVID-19 PANDEMIC IN ZAKAT RECEIVING - Lina Yulianti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Before or during the Covid-19 pandemic, the potential for zakat receipts at the national level is enormous. But unfortunately, the realization of this potential is still minimal and not as expected. Therefore, the National Amil Zakat Agency (BANZAS) utilizes various digital platforms to increase the potential for receiving zakat, especially during the Covid-19 pandemic. This research will be carried out using a qualitative approach and secondary data from various studies or other research. The study results found that zakat receipts through e-commerce always increase every year. Mainly when the Covid-19 pandemic emerged, there were a lot of new zakat givers. This is due to the ease that has been successfully offered by various e-commerce to do zakat so that the acceptance of zakat through ecommerce is continuously increasing.